Narrative Inquiry: Experience and Story in Qualitative Research - Connelly, Michael; Clandinin, Jean (San Francisco Jossey-Bass, 2000)
"The literature on narrative inquiry has been, until now, widely scattered and theoretically incomplete. Clandinin and Connelly have created a major tour de force. This book is lucid, fluid, beautifully argued, and rich in examples. Students will find a wealth of arguments to support their research, and teaching faculty will find everything they need to teach narrative inquiry theory and methods." (Yvonna S. Lincoln, professor, Department of Educational Administration, Texas A&M University)"This book reveals the journey of two scholars who, for the past two decades, have explored the way narrative deepens our understanding of educational experience. Their encounters with seemingly intractable issues provide a model of intellectual courage. Narrative Inquiry invites us to take their journey with them. And it is a journey highly worth sharing." (Elliot W. Eisner, professor of education and art, Stanford University)"An illuminating story of coming to narrative, and of how to proceed with narrative inquiry. This book about the study of experience demonstrates how narrative has emerged from the margins into the center of academic discourse." (Amia Lieblich, professor, Department of Psychology, The Hebrew University)"Their exemplary use of the method in the writing of this text is masterful." (Journal of Curriculum Studies, 2002) --This text refers to an out of print or unavailable edition of this title. Review?Their exemplary use of the method in the writing of this text is masterful.? --Journal of Curriculum Studies, 2002?The literature on narrative inquiry has been, until now, widely scattered and theoretically incomplete. Clandinin and Connelly have created a major tour de force. This book is lucid, fluid, beautifully argued, and rich in examples. Students will find a wealth of arguments to support their research, and teaching faculty will find everything they need to teach narrative inquiry theory and methods.? --Yvonna S. Lincoln, professor, Department of Educational Administration, Texas A&M University?This book reveals the journey of two scholars who, for the past two decades, have explored the way narrative deepens our understanding of educational experience. Their encounters with seemingly intractable issues provide a model of intellectual courage. Narrative Inquiry invites us to take their journey with them. And it is a journey highly worth sharing."--Elliot W. Eisner, professor of education and art, Stanford University